PERAN KOMUNIKASI PERSUASIF DAN INTEGRATED COMMUNICATION MARKETING TERHADAP STRATEGI BERSAING PERUSAHAAN - Surendra, Arya (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
Every company needs to right strategy to send the right massagesabout product or services provided for customuer. Company also needcomunication activity to run the market comunication program. A compnayneeds efektif activity and efisien to get the public attention and for that weread to run program that can be used to reach the company goal. The firstintention from advertising is for selling or to increase the selling of ourproduct, services, and idea. And for that we need the creativity from thebussinesman to choose the right media and right words for customer. Therespon from the advertising not always come in the rardom way that is whythe advertising always repeated it and not only once it be repeate. The pointof the advertising that we make should be having a interesting and clear sothat the customer understand it easily the advertising ussually complicated todo cuery factorhave to be consideration for example the market you wanttoreach. Marketing communications is one of the power for real the gual to sellproduct ond services, for long term purposes or short term purposes.Advertising pusposesis for introducing the product or to brand awarenss,brand images, corporate images and to persuade public/customer to buyproduct and also give information.Keywords: communication, persuasive communication, marketing, competestrategy